Examining Attitudes of Medical Students toward Individuals with Disabilities (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Attitudes of future health professionals is critical to provide inclusive healthcare services. The purpose of this study is to examine attitudes of medical school students toward individuals with disabilities. This study included both quantitative and qualitative analysis of 153 medical school students in Turkey. Results showed that medical students’ comfort levels were significantly more positive toward a patient without apparent disability. The relationship between attitudes and comfort levels for a patient with apparent disability was slightly higher than the relationship between attitudes and comfort levels for a patient without apparent disability. Content analysis of open-ended questions indicated the need of disability education in medical school. Exploration of the attitudes of medical school students toward individuals with disabilities provided both practical and theoretical implications into the field.